A de novo duplication of Xp11.22-p11.4 in a girl with intellectual disability, structural brain anomalies, and preferential inactivation of the normal X chromosome - Holden, Simon T.; Clarkson, Amanda; Thomas, N. Simon; Abbott, Kristin; James, Matthew R.; Willatt, Lionel (The American Journal of Medical Genetics - Part A, 2010)
Only a small number of individuals with duplications within the proximal short arm of the X chromosome have been reported. The majority of patients have duplications encompassing Xp11-p21, or extend more distally into Xp22. We report on a female patient who presented within the first year of life with plagiocephaly, speech delay, and epilepsy. Brain MRI showed a relatively thin cerebral cortex, abnormal periventricular white matter, and abnormal vessels in the left inferior parietal region. Cytogenetic and microsatellite analysis of the patient and her parents showed that she has a de novo duplication of Xp11.22-Xp11.4 on her paternal X chromosome. FISH analysis using fluorescently labeled BACs followed by array analysis including an X tilepath BAC array showed that a 12.3 Mb interval between 40.4 Mb and 52.7 Mb from the Xp telomere (NCBI build 36) was duplicated and excluded the presence of additional rearrangements along the X chromosome. Interestingly, X-inactivation studies in peripheral blood leukocytes showed that the duplicated (paternal) X chromosome was active in the majority of cells, in contrast to other patients with Xp duplications in whom X inactivation is random or skewed toward the normal X. These findings suggest that overexpression of genes from proximal Xp is likely to have contributed to her clinical phenotype.